Partial prevention of calcium paradox in isolated perfused rat hearts by diltiazem - Ziegelhöffer, A; Ravingerová, T; Tribulová, N; Slezák, J; Okolicány, J; Trégerová, V; Krause, E G; Bartel, S (Biomedica biochimica acta, 1989)
It is well known that excessive calcium entry into the myocardial cells may contribute considerably to damage of the heart caused by postischemic reperfusion. The effect of increased calcium entry on hemodynamics, energy metabolism and histochemically estimated enzyme activities in isolated, perfused (Langendorff) rat heart preparation was investigated using calcium paradox (CaPX) as a model. After a 15 min period of stabilized perfusion of the heart, CaPX was induced at 37 degrees C by 2.5 min lasting calcium depletion (calcium-free perfusion) and subsequent calcium repletion (10 min). Changes induced by CaPX concerned loss of electrical and mechanical activities of the heart, significant decreases in coronary flow and ATP, ADP and the total content of adenine nucleotides in tissue as well as considerable depression in ATPases, SDH, beta-HBDH, LDH and glycogen phosphorylase activities in the myocardium. Diltiazem in concentration of 4.0 mumol.l-1 applied prior to calcium depletion and during calcium repletion prevented partially the deterioration of cardiac function by improving contractility and electrical activity of the heart as well as the coronary flow. The effect of diltiazem in concentration of 0.4 mumol.l-1 was less expressed. After both concentrations of diltiazem used, a better preserved ultrastructure, higher activities of the enzymes investigated, significantly higher ATP and total adenine nucleotide levels were seen in the myocardium as compared to the untreated controls.
Keywords: inbrední kmeny potkanů; Rats, Inbred Strains; Rats; In Vitro Techniques; krevní tlak; Myocardial Contraction; Myocardial Reperfusion; vápník; Diltiazem; techniky in vitro; Heart Rate; krysa rodu Rattus; srdeční frekvence; Calcium; diltiazem; zvířata; Blood Pressure; reperfuze myokardu; Heart; Adenosine Triphosphatases; kontrakce myokardu; srdce; adenosintrifosfatasy; Animals